Phosphorus dynamics in permanent pastures: the differential fertilizing and the animal effects - Serrano, João M. (2012)
The general objective of this study was to evaluate the soil phosphate balance over 3 years in a permanent bio-diverse pasture, grazing sheep, and submitted to annual and differential phosphate fertilization. The soil and pasture samples were geo-referenced with RTK GPS and taken in a 6 ha field. This procedure was carried out, each year, from March to May, according to the vegetative growth of the pasture. In October of each year the parcel was fertilized in a differentiated manner, as a function of soil phosphate concentration at the end of the pasture growth cycle (May-June). The phosphorus balance maps in each year were obtained in ARCGIS 9.3 considering: i) the soil phosphate concentration maps; ii) the phosphorus average annual extraction considering the pasture yield; and iii) the differential application maps. The results confirm the difficulties in implementing Precision Agriculture in permanent pastures due to significant temporal variability of soil phosphate concentration and pasture dry matter yield. The results also show the complexity of soil phosphorus dynamics in pastures involving two biological systems: plant and animal, under Mediterranean conditions. The presence of grazing animals adds a notable short-range spatial variation in nutrients that generally arises from heterogeneous excreta depositions.